2021
DOI: 10.1155/2021/2263469
|View full text |Cite|
|
Sign up to set email alerts
|

Severity Assessment of COVID-19 Using a CT-Based Radiomics Model

Abstract: The coronavirus disease of 2019 (COVID-19) has evolved into a worldwide pandemic. Although CT is sensitive in detecting lesions and assessing their severity, these works mainly depend on radiologists’ subjective judgment, which is inefficient in case of a large-scale outbreak. This work focuses on developing a CT-based radiomics model to assess whether COVID-19 patients are in the early, progressive, severe, or absorption stages of the disease. We retrospectively analyzed the CT images of 284 COVID-19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…(20). Compared with previously published models to assess the severity of COVID-19 (21,22,43), our radiomics nomogram showed a very high predictive performance and robustness. Moreover, in addition to building the diagnostic model, this study has also found some interesting insights into CT radiomics.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…(20). Compared with previously published models to assess the severity of COVID-19 (21,22,43), our radiomics nomogram showed a very high predictive performance and robustness. Moreover, in addition to building the diagnostic model, this study has also found some interesting insights into CT radiomics.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to detecting lesions, assessing the grade of COVID-19 pulmonary lesions is important for the hierarchical management and treatment of infected patients (19). However, few studies have focused on the use of AI in grading pulmonary lesions (20), and those that exist have only used "pure" datasets accrued from unified vendor scanners (21,22), which limits the real generalizability of their AI models (23). Thus, it is necessary to develop a more robust AI grading tool based on real-world multicenter datasets.…”
Section: Introductionmentioning
confidence: 99%
“…In AI modelling for prediction, Xu et al . [30] assessed the CT-based model to the predictive ability of the support vector machine for COVID-19 severity in four groups: early, progressive, severe, and absorption. Macro-average of four class-classifications yielded AUCs of 0.97 and 0.9, respectively, for the training and test sets.…”
Section: Discussionmentioning
confidence: 99%
“…Shape features illustrate properties of the size and shape of the images, which was found to be effective in the classification/severity prediction of COVID-19 and pneumonia infections. Indication of shape feature dimensions was suggested to be investigated during each phase of COVID-19 [30, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation